The Influence of Institutional Ownership, Profitability, Liquidity, Dividend Policy, Debt Policy on Firm Value - Sukmawardini, Dewi; Ardiansari, Anindya (Management Analysis Journal, 2018)
The purpose of this study is to determine whether institutional ownership, Return on Assets (ROA), Return on Equity (ROE), current ratio (CR), dividend payout ratio (DPR), and debt to equity ratio (DER) affects the firm value. The population is manufacturing companies which is listed in Indonesia Stock Exchange period 2012-2016. The sample in this study is 14 companies with purposive sampling method. Firm value is proxied by Price to Book Value (PBV), profitability is proxied by Return on Assets  (ROA) and Return on Equity  (ROE), liquidity is proxied by Current ratio (CR), dividend policy is proxied by Dividend Payout Ratio (DPR), and debt policy is proxied by Debt to equity ratio (DER). Methods of data analysis using descriptive statistical analysis and multiple regression analysis by using a eviews 9 program. The result show that th institutional ownership, ROA, and DPR have no effect on firm value, ROE have positive effect on firm value, CR and DER have negative effect on firm value.